Poly[2(6)-aminoazulene]: synthesis, photophysical properties, and proton conductivity. Issue 5 (10th March 2017) - Hou, Ian Cheng-Yi; Shetti, Vijayendra; Huang, Shou-Ling; Liu, Kun-Lin; Chao, Chi-Yang; Lin, Song-Cheng; Lin, You-Jen; Chen, Li-Yin; Luh, Tien-Yau
Abstract : Dimeric aminoazulene and poly[2(6)-aminoazulene] are synthesized by Buchwald–Hartwig coupling of the corresponding monomeric carbamatoaminozulenes followed by hydrolysis. Abstract : Dimeric aminoazulene and poly[2(6)-aminoazulene] are synthesized by Buchwald–Hartwig coupling of the corresponding monomeric carbamatoaminozulenes followed by hydrolysis. The absorption maxima shift from 394 nm for monomeric aminoazulene to 481 nm for the dimer and 591 nm for the polymer. Protonation of the monomeric and polymeric aminoazulenes occurs exclusively at the C1 position(s). The λ max also shows a similar trend at 410, 492 and 670 nm for protonated monomeric, dimeric and polymeric aminoazulenes. These aminoazulenes undergo reversible protonation/deprotonation at the C1 position(s) and both forms exhibit extension of conjugation through amino moieties. Preliminary DFT calculations suggest that the C–N bonds are significantly shortened because of resonance contributions. By incorporating 3 wt% protonated polyaminoazulene in Nafion, the composite membrane has shown 50% reduction in methanol permeability with retention of proton conductivity and 3-fold increment in water permeability, which are advantageous for direct methanol fuel cell application.